Pengaruh Harga, Kualitas Produk, dan Citra Merek Terhadap keputusan Pembelian Produk Sepeda Motor Honda di Kabupaten Bekasi - Aulia Safitri; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo; Matdio Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims (1) to find out whether price has a partial effect on purchasing decisions (2) to find out product quality has a partial effect on purchasing decisions and brand image has a simultaneous effect on purchasing decisions (3) to find out between price, product quality and brand image the most dominant influence on purchasing decisions. The method used in this research is a quantitative method. The results of the research are the multiple linear regression equation Y = 8.636 + 0.337 + 0.014 + 0.117 + ε partially, price has a significant positive effect with a tcount of 4.696, ttable of 0.198045, product quality has a significant positive effect with a tcount of 0.199, ttable of 0.198045, brand image has a positive and significant effect with a t value of1.243 ttable is 0.198045. Simultaneously, price, product quality and brand image influence purchasing decisions with a calculated F value of 9.762. The variable with the most dominant influence in this research is price with a value of 4.696.